Assessment of digestates prepared from maize, legumes, and their mixed culture as soil amendments: Effects on plant biomass and soil properties - Hammerschmiedt, Tereza; Kintl, Antonín; Holatko, Jiri; Mustafa, Adnan; Vitez, Tomas; Malicek, Ondrej; Baltazar, Tivadar; Elbl, Jakub; Brtnicky, Martin (Frontiers in Plant Science, 2022)
Digestate prepared from anaerobic digestion can be used as a fertilizer, as it contains ample amounts of plant nutrients, mainly nitrogen, phosphorous, and potassium. In this regard, digestates produced from mixed intercropped cereal and legume biomass have the potential to enrich soil and plants with nutrients more efficiently than monoculture-based digestates. The objective of this study was to determine the impact of different types of digestates applied at a rate of 40 t·ha-1 of fresh matter on soil properties and crop yield in a pot experiment with lettuce (Lactuca sativa) as a test crop. Anaerobic digestion of silages was prepared from the following monocultures and mixed cultures: broad bean, maize, maize and broad bean, maize and white sweet clover, and white sweet clover. Anaerobic digestion was performed in an automatic custom-made system and applied to the soil. Results revealed that fresh and dry aboveground biomass as well as the amount of nitrogen in plants significantly increased in all digestate-amended variants in comparison to control. The highest content of soil total nitrogen (+11% compared to the control) and urease (+3% compared to control) were observed for maize digestate amendment. Broad bean digestate mediated the highest oxidizable carbon (+48%), basal respiration (+46%), and N-acetyl-β-D-glucosamine-, L-alanine-, and L-lysine-induced respiration (+22%, +35%, +22%) compared to control. Moreover, maize and broad bean digestate resulted in the highest values of N-acetyl-β-D-glucosaminidase and β -glucosidase (+35% and +39%), and maize and white sweet clover digestate revealed the highest value of arylsulfatase (+32%). The observed differences in results suggest different effects of applied digestates. We thus concluded that legume-containing digestates possibly stimulate microbial activity (as found in increased respiration rates), and might lead to increased nitrogen losses if the more quickly mineralized nitrogen is not taken up by the plants.